MULTIFUNCTIONAL ALTERNATIVE ENERGY SYSTEMS ON THE BASIS OF GAS-LIQUID SOLAR COLLECTORS - Doroshenko A.V.; Antonova A.R. (Problems of the Regional Energetics)
The basic circuits of multifunctional solar systems of drainage of air, heating (hot water supply and heating), cooling and air conditioning are developed on the basis of open absorption cycle with direct absorbent regeneration. The basic solutions for new generation of gas-liquid solar collectors are developed.